Public Consultation in Environmental Assessment : Lessons from East and South Asia - World Bank (Washington, DC, 2012)
Consultation is a two-way communication process by which the knowledge and views of affected peoples, NGOs, the private sector and other interested parties are taken into account in development decision-making. In the case of EAs, the assumption is often made that such involvement is not necessary because of the often complex and highly technical nature of environmental impacts. Nevertheless, it is becoming increasingly clear that the knowledge of affected communities and NGOs can contribute to the quality of EAs, as well as provide a better understanding of the social impacts which accompany development interventions. The Bank and other development agencies have learned that if public consultation does not take place early in the project preparation process, it often leads to public misunderstandings, and unnecessary delays in project processing and implementation. The Bank's Operational Directive on EA (OD 4.01) distinguishes between various types of projects based upon the potential significance of their environmental impacts. Category A projects are usually large (e.g., hydro- dams, roads, urban infrastructural projects, industrial facilities, etc.) and have widespread environmental and social impacts, including in some cases involuntary resettlement and effects on vulnerable populations such as indigenous peoples.